2021
DOI: 10.1186/s13287-021-02483-7
|View full text |Cite
|
Sign up to set email alerts
|

Cell therapy in patients with COVID-19 using Wharton’s jelly mesenchymal stem cells: a phase 1 clinical trial

Abstract: Background Mesenchymal stem cells (MSCs) have received particular attention because of their ability to modulate the immune system and inhibit inflammation caused by cytokine storms due to SARS-CoV-2. New alternative therapies may reduce mortality rates in patients with COVID19. This study aimed to assess the safety and efficacy of injecting intravenous Wharton’s jelly-derived MSCs in patients with COVID-19 as a treatment. Methods In this study, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 59 publications
2
56
0
Order By: Relevance
“…5 Many previous studies have shown that administration of mesenchymal stem cells is beneficial in reducing levels of inflammatory markers, such as IL-6 and ferritin. 20,21 Analysis of IL-10 levels in our study showed that the median value of IL-10 on the seventh day after the intervention in the intervention group was lower than in the control group, but there was no significant difference between both groups. In addition, there was a decrease in IL-10 levels on the 14th day after the intervention compared to IL-10 levels before the intervention in the secretome and control groups, and there was no significant difference between both groups.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…5 Many previous studies have shown that administration of mesenchymal stem cells is beneficial in reducing levels of inflammatory markers, such as IL-6 and ferritin. 20,21 Analysis of IL-10 levels in our study showed that the median value of IL-10 on the seventh day after the intervention in the intervention group was lower than in the control group, but there was no significant difference between both groups. In addition, there was a decrease in IL-10 levels on the 14th day after the intervention compared to IL-10 levels before the intervention in the secretome and control groups, and there was no significant difference between both groups.…”
Section: Discussionmentioning
confidence: 52%
“…19,20 Saleh et al (2021) conducted a study on five severe COVID-19 patients who were treated by Wharton's jelly-derived mesenchymal stem cells, and the results were a decrease in IL-6 and VEGF levels and an increase in IL-10 levels after the intervention. 21 Another study conducted by Adas et al (2021) stated that there were a decrease in IL-6 and ferritin levels and an increase in VEGF levels on the seventh day after the intervention with Wharton's jelly-derived mesenchymal stem cells in critically ill COVID-19 patients. 22 Analysis of IL-6 levels in our study showed that the median value of IL-6 in the intervention group was lower than the control group, both on the seventh day and 14 th day after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Phase I and II clinical studies have shown that MSCs transplantation is a safe and potentially effective method for the treatment of moderate to severe ARDS [63,64]. Besides, recent exploratory clinical studies showed that MSCs treatment was associated with improvements in mortality, dyspnea and chest imaging findings for severe and critically ill COVID-19 patients [65][66][67][68][69]. And phase I and II clinical trials have also shown that intravenous MSCs infusion in patients with moderate and severe COVID-19 is safe and well tolerated [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…MSC treatment was found to be safe and well-tolerated by patients. Further studies need to be conducted using control and treatment groups with increased sample sizes in order to draw conclusions about the efficacy of the treatment [ 100 ].…”
Section: Review Of Available Studiesmentioning
confidence: 99%